Study on filling factor of short length screw conveyor with flood-feeding condition. (2018) - Mondal, Debayan; NabenduGhosh,
Abstract: Screw Conveyor is one of the best conveying systems in specific application areas, like mass flow rate less than 1200 t/h while free flowing material as conveying material and it can employed for transportation of pulverized, granular, small-sized lumpy wide range of bulk materials to relatively short distance (Usually up to 40 m for horizontally or to a height up to 30 m). The screw conveyor is a very simple construction with only one moving part, the screw itself with easy maintenance and convenient for intermediate unloading. A screw conveyor can be used for conveying and mixing or blending for more than one material during transportation. To investigate the performance characteristics during transportation of material using continuous type of screw at various speeds, a laboratory sized short length screw conveyor is designed and got fabricated by a suitable vendor.